2109. HHV-6 and EBV Reactivation after Allogeneic Hematopoietic Cell Transplantation in the Era of Letermovir for CMV Prophylaxis: A Retrospective Cohort Study. (15th December 2022) - Kampouri, Eleftheria; Krantz, Elizabeth M; Zamora, Danniel; Kimball, Louise E; Kiem, Erika; Lovas, Erika A; Blazevic, Rachel; Stevens-Ayers, Terry L; Huang, Meei-Li; Masumi, Ueda Oshima; Jerome, Keith R; Zerr, Danielle M; et al.
Abstract: Background: Letermovir (LTV) for CMV prophylaxis in allogeneic hematopoietic cell transplant (HCT) recipients has decreased utilization of broad-spectrum antivirals for CMV, which may result in more frequent reactivation of herpesviruses not targeted by LTV. We hypothesized that the cumulative incidence of HHV-6 and EBV reactivation, and associated diseases, within 100 days after HCT would increase following the introduction of LTV. Methods: We conducted a retrospective study of CMV-seropositive adults who received an allogeneic HCT at our center prior to (5/2015 – 9/2018) and after (10/2018 – 12/2021) routine use of LTV. We reviewed medical records for antiviral use, viral testing, and virus-associated end-organ disease within days 0-100 after HCT. Testing was performed at the discretion of healthcare providers or according to treatment protocols. We computed cumulative incidence estimates treating death and subsequent HCT as competing risks. Results: We identified 403 patients prior to and 378 patients after routine use of LTV. Characteristics were similar between cohorts except for more frequent use of post-transplant cyclophosphamide for GVHD prophylaxis in the LTV cohort. Broad-spectrum antiviral use, as estimated by available data, was 68% pre-LTV versus 23% post-LTV. The incidence of tests for and detection of HHV-6 were similar in both cohorts (Figure 1 ). Two patients in each cohort (0.5%) developed proven or probable HHV-6 encephalitis. Median peak plasma HHV-6 viral load was nearly 1 log10 higher in the LTV cohort (Figure 2 ). The incidence of tests for and detection of EBV was higher in the LTV cohort, but the proportion of patients with ≥ 1 positive test among tested patients was similar (14% pre-LTV vs 20% post-LTV); of note, EBV testing in both cohorts was mainly protocol driven (57% and 50% among tested patients pre- and post-LTV, respectively). There were no cases of PTLD by day 100 in either cohort. Conclusion: Despite a 66% decrease in broad-spectrum antiviral use after the introduction of LTV prophylaxis in CMV-seropositive allogeneic HCT recipients, there was no evidence for increased HHV-6 or EBV reactivation and associated end-organ diseases. Whether the higher peak HHV-6 viral load in the LTV cohort has clinical implications requires further study. Disclosures: Danielle M. Zerr, MD MPH, AlloVir: Advisor/Consultant Michael J. Boeckh, MD PhD, Allovir: Advisor/Consultant|Amazon: Grant/Research Support|Ansun Biopharma: Grant/Research Support|EvrysBio: Advisor/Consultant|Gates Ventures: Grant/Research Support|Gilead Sciences: Advisor/Consultant|Gilead Sciences: Grant/Research Support|GlaxoSmithKline: Advisor/Consultant|GlaxoSmithKline: Grant/Research Support|Helocyte: Advisor/Consultant|Janssen: Advisor/Consultant|Janssen: Grant/Research Support|Kyorin Pharmaceuticals: Advisor/Consultant|Merck: Advisor/Consultant|Merck: Grant/Research Support|Moderna: Advisor/Consultant|Moderna: Grant/Research Support|Regeneron: Grant/Research Support|ReViral: Advisor/Consultant|Symbio: Advisor/Consultant|Takeda: Grant/Research Support|Vir Biotechnology: Advisor/Consultant|Vir Biotechnology: Grant/Research Support Joshua A. Hill, MD, Allovir: Advisor/Consultant|Allovir: Grant/Research Support|Covance/CSL: Advisor/Consultant|CRISPR: Advisor/Consultant|Deverra: Grant/Research Support|Gilead: Grant/Research Support|Karius: Advisor/Consultant|Karius: Grant/Research Support|Merck: Grant/Research Support|Octapharma: Advisor/Consultant|OptumHealth: Advisor/Consultant|Oxford Immunotec: Grant/Research Support|Pfizer: Advisor/Consultant|Symbio: Advisor/Consultant|Takeda: Advisor/Consultant.